Weather And Climate - Time-Life Books (Time-Life Books : Hong Kong, 1994)
This volume explores the fundamentals of atmospheric science and the factors that shape Earth$1 (Bs weather and climate systems: Atmospheric layers and composition Weather patterns, storms, and precipitation Climate zones and long-term climate variability Effects of human activity on climate change Illustrated with photos, diagrams, maps, and easy-to-understand text for young readers.s
Keywords: Meteorolgy